Al-Madāris al-Qurʾāniyyah al-Taqlīdiyyah fī Shamāl Nījīriyyā bayna al-Wāqiʿ wa al-Maʾmūl - Yahaya, Nasir; Waheed, Usman; Adam, Faiz Shuaibu (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
To this day, Qur’anic schools remain one of the main symbols of Islamic identity and an emblem of Islamic civilization and culture. In our Islamic history, schools have contributed positively to building the nation as a result of endowment and funding by individuals or authorities, respectively. This research seeks to shed light on a different model of traditional Quranic schools in northern Nigeria that were able to survive over time in the absence of funding from the government. The research utilized the descriptive analytical approach, drawing on the researcher’s experience as an alumnus of this school. The findings reveal that these schools are still of a Sufi nature and play their role in spreading Islamic culture and religious awareness in Nigerian society. The reason for their survival to the present-day overtime in the absence of funding by the government is because fees are not taken in them officially. Still, instead, It was based on donations and charity. The research recommends that the schools can be developed by eliminating cruelty and harshness when disciplining and prohibiting begging once and for all, in addition to adapting the combination of religious and worldly sciences in the schools.